Current and future approaches in the prevention and treatment of diabetic retinopathy - Louis K Chang (Dove Medical Press, 2008)
Louis K Chang1, David Sarraf1,21Jules Stein Eye Institute, Department of Ophthalmology, University of California, Los Angeles, Los Angeles, CA, USA; 2Department of Ophthalmology, Greater LA VA Healthcare Center, Los Angeles, CAAbstract: Diabetic retinopathy (DR) is a major cause of blindness worldwide and is the number one cause of blindness in working-age individuals in developed countries. We review the current literature and discuss the pathogenesis, modifying risk factors, genetics, and treatment of DR. Special focus is placed on the rationale and effectiveness of therapeutic modalities, both current and future.